2016
DOI: 10.3390/jcm5060056
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Ischemic Stroke and Angiogenic Effects of Chinese Herbal Medicine

Abstract: Stroke is one of the major causes of death and adult disability worldwide. The underlying pathophysiology of stroke is highly complicated, consisting of impairments of multiple signalling pathways, and numerous pathological processes such as acidosis, glutamate excitotoxicity, calcium overload, cerebral inflammation and reactive oxygen species (ROS) generation. The current treatment for ischemic stroke is limited to thromolytics such as recombinant tissue plasminogen activator (tPA). tPA has a very narrow ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 125 publications
(125 reference statements)
1
69
0
Order By: Relevance
“…Currently, effective treatment for ischemic stroke is limited to recombinant tissue plasminogen activator (tPA) [173]. tPA is the only appropriate thrombolytic agent available for acute ischemic stroke treatment [174,175].…”
Section: Micrornas As Possible Therapeutic Agentsmentioning
confidence: 99%
“…Currently, effective treatment for ischemic stroke is limited to recombinant tissue plasminogen activator (tPA) [173]. tPA is the only appropriate thrombolytic agent available for acute ischemic stroke treatment [174,175].…”
Section: Micrornas As Possible Therapeutic Agentsmentioning
confidence: 99%
“…Local resident microglia can secrete proangiogenesis cytokines such as interleukin‐6 (IL‐6), IL‐1α, vascular endothelial growth factor(VEGF), matrix metalloproteinase (MMP) and nitric oxide . The role of microglia on the post–stroke neurovascular unit largely depends on the phenotype of microglia.…”
Section: The Role Of Neuroinflammation In Multiple Brain Repair Mechamentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic autoimmune and inflammatory disease that can cause pain, disability and premature death. It is reported that RA could be treated and controlled effectively using antirheumatic HDSs . With the growing interest in the development of antirheumatic HDSs, the quality control of these drugs is a challenging task, especially detection of synthetic antirheumatic drugs in HDSs …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that RA could be treated and controlled effectively using antirheumatic HDSs. [4][5][6] With the growing interest in the development of antirheumatic HDSs, the quality control of these drugs is a challenging task, especially detection of synthetic antirheumatic drugs in HDSs. 1,4 Various analytical techniques based on chromatography, spectroscopy, bioassays, mass spectrometry, capillary electrophoresis, and other successful methods have been used for determination of synthetic drugs in adulterated HDSs.…”
Section: Introductionmentioning
confidence: 99%